Al modification as indicator of current filaments in IGBTs under repetitive SC operation. Issue 15 (1st December 2019) - Mysore, Madhu Lakshman; Bhojani, Riteshkumar; Kowalsky, Jens; Lutz, Josef; Baburske, Roman; Schulze, Hans‐Joachim; Niedernostheide, Franz‐Josef
Abstract : This work investigates modification on the top‐side aluminium (Al) metallisation of 1.2 kV insulated‐gate bipolar transistors (IGBTs) under repetitive short‐circuit (SC) type‐I measurements for two different parasitic inductances of 45 and 380 nH. The presence of current–density filaments starting at the collector side during SC leads to local temperature increase of the emitter metallisation and thus to modification of the top Al surface in the pattern of the current filaments. Here, two techniques thermo‐reflectance microscopy, which can detect the surface temperature during repetitive short circuits directly and Al modifications after repetitive SC with analysis under optical microscope after the test have been considered. At 45 nH, with different DC‐link voltages from 300 to 600 V, the Al modification pattern is non‐uniform and it becomes uniform for V DC >600 V. However, for 380 nH parasitic inductance and for DC‐link voltages 300 and 400 V, the Al reconstruction shows a non‐uniform pattern and becomes uniform for V DC ≥500 V. The SC simulations were performed by using a simplified front‐side IGBT structure using variable DC‐link voltages and inductances to reproduce the filament behaviour.